Penyusunan Muatan dan Media Pendamping untuk Pembelajaran Matematika Paket B PKBM El Fataa Banyuwangi - Putri, Eka Maulya; Sulistianingrum, Nilam; Setiawan, Galih; Sulistyani, Yulia; Yanti, Diana Ainun Dwi; Hidayah, Risma; Hariastuti, Rachmaniah Mirza (Jurnal PKM: Pengabdian Kepada Masyarakat, 2024)
This community service activity is aimed at assisting the implementation of learning (especially mathematics at B level) at PKBM El Fataa. Activities are based on the conditions of PKBM which has just been established and tutors who have no teaching experience. In accordance with the scientific basis of implementing the activities, this program is focused on mathematics learning related to the preparation of content and learning media.The program is also focused on B level because it contains the most students. The results of the activity show that the mathematics learning content for B level, which has been prepared by the implementing team, can be adjusted to the learning program at PKBM El Fataa. The accompanying learning media is also in accordance with the learning content and needs of the learning community. The application of content and media in mathematics learning will be monitored by the activity implementation team periodically as evaluation material.